Ernst Ludwig Kirchner’s View of Gender Roles Based on His Woodcut Cycle on Petrach’s Triumph of Love - Bonnefoit, Régine (Munich: Hirmer, 2020)
The History of the Creation of Kirchner's illustrations for Petrach's Triumph of Love. In them Kirchner pictured the development of his own relationship with Erna Schilling, his companion from 1912 until his suicide in 1938. Since a majority of the eight woodcuts picture the "conflicts" Kirchner mentions, their content can be classed under the rubric "Battle of the Sexes.”. This subject, introduced in literature, has dominated painting, sculpture, and music since the mid-nineteenth century.
Keywords: Ernst Ludwig Kirchner; gender roles; battle of sexes; Petrach; Triumph of Love; Edvard Munch